Population planning in India : policy issues and research priorities - Bose, Ashish (ed.); Desai,P.B. (Ed.) (Delhi, 1989)
The Indian Association for the study of Population (IASP) brought together several well-known demographers from abroad, Indian scholars and administrators in charge of the family planning programme, in a free-wheeling symposium held in New Delhi (February 1988). Instead of seeking research papers, the organisers looked for ideas on emerging issues, new initiatives and research priorities which could eventually contribute to a more effective formulation and implementation of India's family. planning programme. The need for a continuing dialogue between scholars and administrators was also highlighted at the 20th International Conference on Population, organised by IUSSP at Florence in 1985. This book makes a modest attempt to reflect the perceptions of individual scholars and administrators in regard to a number of policy issues in the Indian context. It is hoped that this will be a starting point in a more substantial Indian contribution through papers research for the 21st International Population Conference of IUSSP (New Delhi, September 1989).
Keywords: Population